Anthropogenic and environmental influences on nutrient accumulation in mangrove sediments. (April 2021) - Pérez, Alexander; Machado, Wilson; Sanders, Christian J.
Abstract: Here we provide a global review on nutrient accumulation rates in mangroves which were derived from sixty-nine dated sediment cores, addressing environmental and anthropogenic influences. Conserved mangroves presented nitrogen and phosphorous accumulation rates near to 5.8 ± 2.1 and 0.8 ± 0.5 g m −2  yr −1, respectively. These values were significantly lower than those observed for mangroves impacted by coastal eutrophication, which were found to bury 21.5 ± 8.6 and 17.9 ± 2.4 g m-2 yr −1, of nitrogen and phosphorous respectively. Moreover, higher nutrient accumulation rates were found in mixed mangroves as compared to monospecific forests, and higher values were noted within vegetated areas as compared to mudflats. For South America and Asia, mangroves impacted by anthropogenic activities may result in up to seventeen-fold higher nitrogen and phosphorous accumulation rates in comparison with values under conserved conditions. For Oceania, these differences may be up to fivefold higher in impacted as compared to the conserved ecosystems in this region. Graphical abstract: Unlabelled Image Highlights: A research of N and P accumulation rates in mangrove sediments was performed. Nutrient accumulation rates are higher in mangrove sediments than in bare mudflats. Impacted mangroves presented up to four-fold higher N accumulation rates. Impacted mangroves presented up to twenty-fold higher P accumulation rates.